EFFECT OF TRIJODOTHYRONINE ON LIPID PER OXIDATION AND LNER ENZYME VALUES ON ISCHEMIC LIVER INJURY IN RATS - Ömer ŞAKRAK,; Abdullah SAĞLAM,; Hatice PAŞAOĞLU,; Figen ÖZTÜRK,; Ahmet TUTUŞ,; Oktay BANLI,; Yücel ARITAŞ,; Yaşar YEŞİLKAYA, (Turkish Journal of Gastroenterology, 2020)
-